Microestruturas de zeína produzidas pela técnica de fiação por sopro em solução visando à incorporação e liberação lenta de vitamina C - Scagion, Vanessa Priscila (2019)
The development of functional micro/nanostructures for use in the agricultural area is relevant and has the potential to reduce the consumption of inputs with improved efficiency of the final product. In this context, the production of polymeric structures by solution blow spinning (SB-Spinning) has been proposed as a valuable technique for allowing the production of fibrous structures in micro/nanometric scale with high production rate and in-situ applications. Currently, SB-Spinning has been mostly used in the production of fibers, which are used purely or as a matrix for carrying chemical additives to provide the fiber more functionalities for varied applications. This work aims to evaluate the use of SB-Spinning technique in the production of micro/nanostructures of zeins as fibers and particles, aiming to use them as matrices for incorporation of vitamin C for slow release applications, which find application in fish dietary. Two structures were obtained as fibers and "bags" (particles), being thus evaluated the rheological behavior of the polymer solutions, in order to understand how such structures were formed. The "bags" were chosen to be used as a model of incorporation of vitamin C presenting an incorporation efficiency of about 73,3%, besides having a fast release (5 minutes). In addition, the produced structures presented a reproducible release profile, showing potential for the production of systems for the incorporation and release of vitamin C, preserving their physical and chemical characteristics.